2016
DOI: 10.1111/isj.12113
|View full text |Cite
|
Sign up to set email alerts
|

Starting open source collaborative innovation: the antecedents of network formation in community source

Abstract: Specific needs in the area of enterprise applications have led to a new type of collaborative open source innovation development across institution borders: community source. We use the Kuali community source network, a jointly managed, border‐spanning organization that supplies the institutions that created it, to describe how community source works. This study builds a theoretical basis for understanding the individual and institutional factors affecting community source network formation and the decision by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 93 publications
0
19
0
1
Order By: Relevance
“…International entrepreneurship studies have identified two factors that appear to be important to this process: (1) information diversity, the degree to which firms draw information from multiple sources in the decision-making process, affecting the quality and quantity of available knowledge (Fiet & Patel, 2008;Gielnik, Krämer, Kappel, & Frese, 2014;Heirati & O'Cass, 2016), and (2) innovativeness, the tendency to introduce new products or services, which reflects how accumulated knowledge is applied (Cavusgil & Knight, 2015;Knight & Cavusgil, 2004). Entrepreneurial information is available in an increasing number of channels as information technology advances, making the range of sources broader and more significant (Liu, Hull, & Hung, 2017). Being innovative can help firms develop capabilities (e.g., conducting market research with new potential customers) they need to compete in a foreign market (Cavusgil & Knight, 2015;Knight & Cavusgil, 2004;Mathews, 2006).…”
mentioning
confidence: 99%
“…International entrepreneurship studies have identified two factors that appear to be important to this process: (1) information diversity, the degree to which firms draw information from multiple sources in the decision-making process, affecting the quality and quantity of available knowledge (Fiet & Patel, 2008;Gielnik, Krämer, Kappel, & Frese, 2014;Heirati & O'Cass, 2016), and (2) innovativeness, the tendency to introduce new products or services, which reflects how accumulated knowledge is applied (Cavusgil & Knight, 2015;Knight & Cavusgil, 2004). Entrepreneurial information is available in an increasing number of channels as information technology advances, making the range of sources broader and more significant (Liu, Hull, & Hung, 2017). Being innovative can help firms develop capabilities (e.g., conducting market research with new potential customers) they need to compete in a foreign market (Cavusgil & Knight, 2015;Knight & Cavusgil, 2004;Mathews, 2006).…”
mentioning
confidence: 99%
“…At the same time, open innovation aims to provide information and knowledge through quality sources [Ramírez-Montoya, García-Peñalvo, 2018;Smith, Seward, 2017;Cooke, 2017;Gold, 2016;Viseur, 2015;Sánchez-González, Herrera, 2014;Freitas, Dacorso, 2014;Azmi, Alavi, 2013;Simeth, Raffo, 2013;Stodden, 2010]. Thus, it manages the results of production through collaborative networks and, eventually, through social networks for users [Vrgovic et al, 2012;Liu et al, 2017]. Therefore, learning about academic information enables the understanding of the context and create strategies to overcome the challenges.…”
Section: Intersection Between Open Science and Open Innovationmentioning
confidence: 99%
“…Развитие ОИ в целях предоставления информации и знаний на основе качественных источников [Ramírez-Montoya, García-Peñalvo, 2018;Smith, Seward, 2017;Cooke, 2017;Gold, 2016;Viseur, 2015;Sánchez-González, Herrera, 2014;Freitas, Dacorso, 2014;Azmi, Alavi, 2013;Simeth, Raffo, 2013;Stodden, 2010] порождает у участников определенное восприятие производства и актуальности полученных знаний. Ход и результаты этого процесса определяются механизмами сотрудничества, т. е. в конечном счете -социальными сетями пользователей [Vrgovic et al, 2012;Liu et al, 2017]. Научные данные позволяют осмыслить контекст и разработать стратегию преодоления вызовов.…”
Section: пересечение открытой науки и открытых инновацийunclassified